Mature natural killer cells reset their responsiveness when exposed to an altered MHC environment - Joncker, Nathalie T. (The Rockefeller University Press, 2010)
Some mature natural killer (NK) cells cannot be inhibited by major histocompatibility complex (MHC) I molecules, either because they lack corresponding inhibitory receptors or because the host lacks the corresponding MHC I ligands for the receptors. Such NK cells nevertheless remain self-tolerant and exhibit a generalized hyporesponsiveness to stimulation through activating receptors. To address whether NK cell responsiveness is set only during the NK cell differentiation process, we transferred mature NK cells from wild-type (WT) to MHC I–deficient hosts or vice versa. Remarkably, mature responsive NK cells from WT mice became hyporesponsive after transfer to MHC I–deficient mice, whereas mature hyporesponsive NK cells from MHC I–deficient mice became responsive after transfer to WT mice. Altered responsiveness was evident among mature NK cells that had not divided in the recipient animals, indicating that the cells were mature before transfer and that alterations in activity did not require cell division. Furthermore, the percentages of NK cells expressing KLRG1, CD11b, CD27, and Ly49 receptors specific for H-2(b) were not markedly altered after transfer. Thus, the functional activity of mature NK cells can be reset when the cells are exposed to a changed MHC environment. These findings have important implications for how NK cell functions may be curtailed or enhanced in the context of disease.